2020
DOI: 10.1155/2020/5036396
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Pharmacological Revascularization Strategies for Prevention of Microvascular Dysfunction in ST-Segment Elevation Myocardial Infarction: Analysis from Index of Microcirculatory Resistance Registry Data

Abstract: Objectives. We aimed to identify mechanical and pharmacological revascularization strategies correlated with the index of microcirculatory resistance (IMR) in ST-elevation myocardial infarction (STEMI) patients. Background. Microvascular dysfunction (MVD) after STEMI is correlated with infarct size and poor long-term prognosis, and the IMR is a useful analytical method for the quantitative assessment of MVD. However, therapeutic strategies that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In their study, Khan et al showed that microvascular injury was more reduced in the third-generation P2Y 12 inhibitor group. Results published by Jang et al support the claim that third-generation P2Y 12 inhibitors are more effective in lowering the IMR value than clopidogrel in patients with STEMI [ 45 ].…”
Section: Discussionmentioning
confidence: 69%
“…In their study, Khan et al showed that microvascular injury was more reduced in the third-generation P2Y 12 inhibitor group. Results published by Jang et al support the claim that third-generation P2Y 12 inhibitors are more effective in lowering the IMR value than clopidogrel in patients with STEMI [ 45 ].…”
Section: Discussionmentioning
confidence: 69%
“…Prolonged contrast elution has been considered a classic angiographic marker of coronary microvascular damage, introducing the concept of TMPG. 23 Jang et al 28 conducted a study evaluating coronary microvascular dysfunction in patients with STEMI and found that TMPG was more sensitive than TIMI for screening out microvascular dysfunction. Jia et al 29 adopted TMPG of the intervened vessel to evaluate the benefits of high-dose statins on improving coronary microcirculation in patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…23 Jang et al. 28 conducted a study evaluating coronary microvascular dysfunction in patients with STEMI and found that TMPG was more sensitive than TIMI for screening out microvascular dysfunction. Jia et al.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Jang and De Luca et al found that high Killip grade was associated with a high coronary microcirculation resistance index and myocardial reperfusion injury. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%